Library discovery systems and their users: a case study from Curtin University Library - Wells, David (Australian Library and Information Association, 2016)
Discovery systems are now increasingly the dominant technology through which clients discover and access the information resources held by academic and research libraries. However, as yet, little work has been done to explore the use and impact of discovery systems on user behaviour. This article examines transactional logs from the Ex Libris Primo installation of Curtin University Library sampled between 2013 and 2015, together with the results of a user survey conducted in 2014, to investigate actual patterns of use and perceptions of value in the available discovery system functionality. The evidence collected supports the original contention of discovery system designers that the single-search box approach adopted by Google and other internet search engines is an appropriate form for library catalogue design. On the other hand, discovery system users clearly value functionality corresponding to traditional library tasks over attempts to locate the catalogue in the conceptual framework of social media.